1999
DOI: 10.1007/bf02482235
|View full text |Cite
|
Sign up to set email alerts
|

Expression of nm23-H1 in colorectal cancer: No association with metastases, histological stage, or survival

Abstract: The correlations of nm23-H1 expression in primary cancer lesions with the already confirmed 14 prognostic variables and survival were examined in 52 advanced colorectal cancer patients, because the clinical roles of nm23-H1 expression in the cancer lesions remain controversial. An immunohistochemical expression of nm23-H1 was found in 23 lesions (positive group) but not found in 29 lesions (negative group). No significant difference between the positive and negative groups was found according to 12 clinicopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
1
2
0
1
Order By: Relevance
“…We found a TP53 overexpression frequency of 48% (77/160); other authors report results in CRCs ranging from 42% to 74% (Auvinen et al 1994;Bouzourene et al 2000;Jansson et al 2001;Kaserer et al 2000;Scott et al 1991). Moreover, our results showed NM23-H1 expression in 66% meo et al 2000;Lee et al 2001;Nesi et al 2001;Sarris et al 2001;Tabuchi et al 1999). Variability in TP53 and NM23-H1 immunoreactivity is mainly due to tumoral heterogeneity and the specific features of the patient cohorts included in the study, such as histopathologic staging, grading, and site of the tumor.…”
Section: Discussionsupporting
confidence: 57%
“…We found a TP53 overexpression frequency of 48% (77/160); other authors report results in CRCs ranging from 42% to 74% (Auvinen et al 1994;Bouzourene et al 2000;Jansson et al 2001;Kaserer et al 2000;Scott et al 1991). Moreover, our results showed NM23-H1 expression in 66% meo et al 2000;Lee et al 2001;Nesi et al 2001;Sarris et al 2001;Tabuchi et al 1999). Variability in TP53 and NM23-H1 immunoreactivity is mainly due to tumoral heterogeneity and the specific features of the patient cohorts included in the study, such as histopathologic staging, grading, and site of the tumor.…”
Section: Discussionsupporting
confidence: 57%
“…Tabuchi et al showed nm23-H1 expression in 44% of colorectal cancers, but an association with metastasis, histological stage, or survival was not found. 38 Zeng and co-workers examined the expression of nm23-H1 in colorectal cancer and liver metastases, and correlated nm23-H1 expression with clinicopathological variables. No significant association was seen between the amount of nm23-H1 RNA and the patient's age or sex, tumour location, differentiation, presence of lymph node involvement, or distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting observations have been reported. Allelic deletion or mutation of the nm23‐H1 gene appears to be associated with distant metastasis in some studies;13, 14, 15, 16 on the other hand, there are several studies that denied the correlation between the progression of colorectal carcinogenesis or distant metastasis and nm23‐H1 expression 17, 18, 19…”
mentioning
confidence: 99%